2020
DOI: 10.1002/lsm.23314
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of a Novel 730 nm Picosecond Titanium Sapphire Laser for the Treatment of Benign Pigmented Lesions

Abstract: Background and Objectives Picosecond lasers in dermatology were originally focused on optimizing the removal of unwanted tattoos. Subsequent advances in this technology have expanded its clinical indications to include treatment of benign pigmented lesions, photodamage, melasma, and scar revision. In this retrospective review, we evaluate a novel 730 nm picosecond titanium sapphire laser in treating benign pigmented lesions. Study Design/Materials and Methods This is a retrospective review of all patients who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 37 publications
0
5
3
Order By: Relevance
“…The PIH rate in previous studies on PSL treatment for pigmentary lesions was 5%-10%. 16 The PIH rates observed in this study were 3.49% and 4.65% for the 730 and 755 nm PSLs, respectively, which were slightly lower than the estimated 5%-10% mentioned above. The PIHo rates in our study were 8.14% and 9.3% for the 730 and 755 nm PSLs, respectively, corresponding to the 2.78%-9% PIHo rate previously reported for other PSLs.…”
Section: Discussioncontrasting
confidence: 62%
See 3 more Smart Citations
“…The PIH rate in previous studies on PSL treatment for pigmentary lesions was 5%-10%. 16 The PIH rates observed in this study were 3.49% and 4.65% for the 730 and 755 nm PSLs, respectively, which were slightly lower than the estimated 5%-10% mentioned above. The PIHo rates in our study were 8.14% and 9.3% for the 730 and 755 nm PSLs, respectively, corresponding to the 2.78%-9% PIHo rate previously reported for other PSLs.…”
Section: Discussioncontrasting
confidence: 62%
“…6 Lipp et al have retrospectively reviewed 24 patients with benign pigmented lesions treated with 730 nm PSL, with improvement in pigmentation observed in 86% of the patients, whereas 3% showed no improvement, and 11% had worsening of pigmentation. 16 Loh et al have presented two cases demonstrating a novel application of 730 and 785 nm PSL in dealing with the nevus of Ota, and both showed >75% clearance. 9 Moreover, Kauvar et al have reported 20 patients with facial and nonfacial freckles treated with 730 nm PSL; 74% of patients had a lesion clearance >50%, whereas 36% of patients had a lesion clearance >75% at the 12-week follow-up.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thirty‐one percent had ≥70% improvement and 60% had ≥50% improvement and PIH occurred in 11% of subjects. 28 In this study, the mean beam diameter used was 2.4 mm and the mean fluence was 3.12 J/cm 2 .…”
Section: Discussionmentioning
confidence: 93%